Particle size influence on material properties of BaTiO3 ceramics fabricated using freeze-form extrusion 3D printing. (16th October 2019) - Renteria, Anabel; Diaz, Jorge A; He, Baitong; Renteria-Marquez, Ivan A; Chavez, Luis A; Regis, Jaime E; Liu, Yingtao; Espalin, David; Tseng, Tzu-Liang (Bill); Lin, Yirong
Abstract: Barium titanate (BaTiO3 ; BTO) is a well-known lead-free piezoelectric material commonly used for sensors and actuators applications. There are several traditional methods to fabricate bulk BTO ceramics; however, most of those methods have restrictions regarding being able to produce a functional and complex shape for specific application needs. Recently, additive manufacturing techniques such as binder jetting have enabled the fabrication of complex designs of piezoelectric ceramics. However, the density achieved is relatively low thus narrowing their applications. This paper presents the fabrication of high-density BaTiO3 ceramics using Freeze-form Extrusion Fabrication (FEF). The influence on material properties for different ceramic particle size was assessed. It was found that parts printed using finer BaTiO3 particle sizes achieved better results in terms of density, piezoelectric, and dielectric properties. For this study, the 100 nm BaTiO3 samples achieved 85.24% density, a high piezoelectric property of 204.61pC/N and dielectric permittivity of 2551. These results demonstrated the feasibility of using FEF additive manufacturing to fabricate high-quality functional ceramics with designed geometry in a mold-free fashion.